Liminalitas dan Ambivalensi dalam Novel Burung-Burung Manyar Karya Y.B. Mangunwijaya: Poskolonialisme Homi K. Bhabha - Nensilianti, Nensilianti; Ridwan, Ridwan; Istiqamah, Putri Nur (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
This research reviews the concepts of liminality and ambivalence in the novel Burung-Burung Manyar by Y.B. Mangunwijaya using a qualitative descriptive approach. The analysis describes how the two concepts are reflected in the narrative, characters, and themes of the novel. The results of the analysis show that the characters in the novel experience liminality, being on the verge of transition between two different identities or cultures, as well as ambivalence, with mixed feelings between emotions and beliefs. The novel depicts the complexity of the relationship between colonials and colonists and the individual's experience of self-discovery in the midst of cultural and social conflict.